Innovation Capability and Learning Capability To Individual Performace : Well Being Moderation (Case Study of Small and Medium Enterprises: Freez Food Baby Porridge Sedati) - Fransisca Eri Yulianti; Wahyu Eko Pujianto (Faculty of Social and Political Science, 2024)
This study aims to investigate the relationship between innovation capability, learning capability, and individual performance in Small and Medium Enterprises (SMEs) with well-being moderation, using the Case Study of